Sintesis nanopartikel zirkonium dioksida (ZrO2) dengan metode sol gel menggunakan ekstrak nanas sebagai pengkelat untuk aplikasi nanofluida pendingin - Dini Talenti Arya (PILLAR OF PHYSICS, 2016)
The study of the nanoparticles is rapidly growing in the industry. The application of nanoparticles is very useful in improving the thermal conductivity of the fluid coolant such as water and oil that are still low. Efforts should be made to improve the thermal conductivity of the cooling fluid by mixing nanoparticles into the basic fluid that is called Nanofluids. This study aimed to determine the effect of pineapple’s extract on the characteristics of nanoparticles of Zirconium Dioxide (ZrO2) in terms of phase and the value of the surface area of the particles of Zirconium Dioxide (ZrO2) by one gram of it and see the effect the composition of nanoparticles suspended in a fluid on viscosity, zeta potential increase in thermal conductivity. This research is an experimental research that is conducted at the Laboratory of Science Techno Centre of Science Nuclear Applied and Technology (PSTNT) National Nuclear Energy Agency (BATAN) Bandung. The synthesis was conducted by using sol gel with calcination temperature of 700 , ZrO2 powder obtained then characterized by using XRD and Surface Area Analyzer. Furthermore, Zirconium Dioxide (ZrO2) nanoparticles mixed into 100 ml of distilled water and characterized using test equipment Viscosity, Zeta Potential meter and Critical Heat Flux (CHF). Results obtained in the study was the effect of the addition of pineapple extract as chelating against nanoparticles of zirconium dioxide (ZrO2) to prevent agglomeration/buildup on the particles of Zirconium Dioxide (ZrO2). The next result is the effect of the composition of nanoparticles of ZrO2 that were suspended in 100 ml of distilled water to the value of fluid Viscosity, Zeta Potential and rise of Critical Heat Flux. The bigger composition ZrO 2 led to a rise to the viscosity of Nano fluids water-ZrO2, the increase in the value of zeta potential and the increase of the value of Critical Heat Flux (CHF) associated with thermal conductivity values. The more viscous a fluid with the presence of nanoparticles, the conductivity value will be higher. High conductivity will improve the quality of the cooling fluid